Bacterial infection of macrophages induces decrease in refractive index. Issue 5 (6th August 2012) - Ekpenyong, Andrew E.; Man, Si Ming; Achouri, Sarra; Bryant, Clare E.; Guck, Jochen; Chalut, Kevin J.
Abstract Infection of cells by pathogens leads to both biochemical and structural modifications of the host cell. To study the structural modifications in a label‐free manner, we use digital holographic microscopy, DHM, to obtain the integral refractive index distribution of cells. Primary murine bone marrow derived macrophages (BMDM) infected with Salmonella enterica serovar Typhimurium, undergo highly significant reduction in refractive index, RI, compared to uninfected cells. Infected BMDM cells from genetically modified mice lacking an inflammatory protein that causes cell death, caspase 1, also exhibit similar decrease in RI. These data suggest that any reduction in RI of Salmonella ‐infected BMDMs is pathogen induced and independent of caspase 1‐induced inflammation or cell death. This finding suggests DHM may be useful for general real time monitoring of host cell interactions with infectious pathogens. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)